Short-term Outcomes of Open “Crown” Type v. Percutaneous Bunnell Type Repair of Acute Achilles Tendon Ruptures. Randomized Control Study - Makulavičius, Aleksas; Mazarevičius, Giedrius; Masionis, Povilas; Urmanavičius, Matas; Klinga, Mindaugas; Uvarovas, Valentinas; Porvaneckas, Narūnas (Lietuvos chirurgija, 2020)
Background. The optimal treatment of acute Achilles tendon ruptures is still under debate. The purpose of this randomized controlled trial was to evaluate outcomes of open repair comparing with percutaneous procedure for Achilles tendon ruptures. Methods. 100 patients with acute Achilles tendon rupture were randomized in two groups: open “crown” type (group A) and percutaneous Bunnell type repair (group B). Absorbable suture was used in both groups. 87 patients were available for the mean follow up of 6 months. Results. No statistically significant difference was observed between groups in ATRS (Achilles Tendon Total Rupture Score), leg circumference, single heel rise, Achilles resting angle, time back to work and sports and overall patient satisfaction. Percutaneous technique was much faster. Overall 13 complications occurred in both groups (5 and 8 respectively). No deep infection occurred, no revisions were needed. Conclusions. Both techniques showed to be effective and safe when using absorbable suture material with a high patient satisfaction and a low complication rate, but percutaneous repair was significantly faster.